TRAINING, MANAGERIAL SKILLS, AND PRINCIPAL PERFORMANCE AT SENIOR HIGH SHOOL IN NORTH LUWU REGENCY - Hilal Mahmud; Syamsu Sanusi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The principal needs training to have managerial skills to optimize his performance. Otherwise, several studies have shown the opposite. This study aims to examine the effect of exercise and managerial skills on principal performance. This study is field research with a simple path analysis design. Data were obtained through questionnaires, observation, and documentation study. This study shows that there is an effect of training and principal managerial skills on principal performance. This indicates that the more intense the principal attends training and has a deep understanding of training material, the higher the principal organizational skills are. The higher the principal managerial skills are, the higher the quality of the principal performance is, which in turn increases the rate of the school.